2020
DOI: 10.1096/fj.201902683r
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TMPO‐AS1 promotes LCN2 transcriptional activity and exerts oncogenic functions in ovarian cancer

Abstract: Ovarian cancer remains the sixth most frequently occurring cancer in women worldwide. Long noncoding RNAs (lncRNAs) are capable of regulating gene expression, and thus, participating in a wide range of biological functions and disease processes including cancer development. Our work suggests that lncRNA TMPO antisense RNA 1 (TMPO‐AS1) represents an oncogenic lncRNA in ovarian cancer and presents a novel mechanism involving transcription factor E2F transcription factor 6 (E2F6) and lipocalin‐2 (LCN2). We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…LncRNAs are also involved in DNA repair, cell proliferation, and EMT through regulating the expression of various genes linked to carcinogenesis and tumor progression. TMPO-AS1 was demonstrated to have abnormal expression in breast cancer (Mitobe et al, 2020), cervical cancer (Zhao et al, 2020), and ovarian cancers (Li et al, 2020a). In triple-negative breast cancer, the upregulation of TMPO-AS1 was associated with tumor proliferation-related biomarkers.…”
Section: Breast Cervical and Ovarian Cancersmentioning
confidence: 98%
See 1 more Smart Citation
“…LncRNAs are also involved in DNA repair, cell proliferation, and EMT through regulating the expression of various genes linked to carcinogenesis and tumor progression. TMPO-AS1 was demonstrated to have abnormal expression in breast cancer (Mitobe et al, 2020), cervical cancer (Zhao et al, 2020), and ovarian cancers (Li et al, 2020a). In triple-negative breast cancer, the upregulation of TMPO-AS1 was associated with tumor proliferation-related biomarkers.…”
Section: Breast Cervical and Ovarian Cancersmentioning
confidence: 98%
“…TMPO-AS1 was reported to be significantly upregulated in various cancers, such as lung cancer (Yu et al, 2020), breast cancer (Mitobe et al, 2020), colorectal cancer (CRC) (Mohammadrezakhani et al, 2020), hepatocellular carcinoma (HCC) (Liu and Shen, 2020;Wang et al, 2020), gastric cancer (GC) (Sun and Han, 2020), bladder cancer (He et al, 2020b), laryngeal squamous cell carcinoma (LSCC) (Zhang et al, 2020b), ovarian cancer (Li et al, 2020a;Zhao et al, 2020), thyroid cancer (Li et al, 2020b), esophageal cancer (Gao et al, 2020), Wilms tumor (Zhang et al, 2020a), cervical cancer (Gang et al, 2020), retinoblastoma (Peng et al, 2020), osteosarcoma (Cui and Zhao, 2020), or prostate cancer (Huang et al, 2018), and functions as an oncogene in carcinogenesis and tumor progression. To further investigate the aberrant expression of TMPO-AS1 in various cancers and their associated prognosis, this study applied the Gene Expression Profiling Interactive Analysis (GEPIA) online data analysis tool (Tang et al, 2017).…”
Section: Tmpo-as1 Functions As Oncogenic Lncrna In Various Cancersmentioning
confidence: 99%
“…6 Zhao et al reported that silence of TMPO-AS1 restrained the aggressiveness and the pro-angiogenic activity of ovarian cancer cells, blocking ovarian cancer development. 17 In the present study, we first discovered the increase of lncRNA-TMPO-AS1 in glioma cell lines, and further cellular function assay disclosed that knockdown of TMPO-AS1 could suppress glioma cell proliferation, colony formation, migration and invasion, demonstrating the oncogenic activity of TMPO-AS1 in glioma. The crosstalk between lncRNAs and miRNAs is common in cancer biology.…”
Section: Discussionmentioning
confidence: 62%
“…The authors demonstrated that DLX6-AS1 acts by sponging the miR-195-5p and upregulating its miRNA-target FHL2 (four and a half LIM domains 2). Likewise, TMPO-AS1 (thymopoietin antisense RNA 1) knockdown significantly suppressed OC cell proliferation, migration, invasion, and angiogenesis, also inhibiting tumorigenesis and angiogenesis in vivo [26]. TMPO-AS1 was found to be upregulated in OC cell lines and clinical samples and exerts its oncogenic role by binding to E2F6 (E2F transcription factor 6) and modulating its occupancy on the promoter region of LCN2 (lipocalin 2), whose expression is activated.…”
Section: Lncrnas and Their Association With Ovarian Cancermentioning
confidence: 99%
“…The interplay between differentially expressed lncRNAs, such as MALAT1 (metastasis-associated lung adenocarcinoma transcript 1) and CDKN2B-AS1 (cyclin-dependent kinase inhibitor 2B antisense RNA 1), and histone-modifying or chromatin-remodeling complexes has been implicated in transcriptional regulation, enabling progression of different cancer types [24]. A set of the OC-related lncRNAs acts as oncogenes or tumor suppressors, contributing to cellular transformation [25][26][27].…”
Section: Introductionmentioning
confidence: 99%